PENGARUH PERSEPSI TENTANG HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP VOLUME PENJUALAN PAKET WISATA KARIMUNJAWA DI BIRO TOUR DAN TRAVEL KARIMUNJAWA BEACH ADVENTURE - Sulthon Darmawan, Tommy; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2015)
The research was triggered by increasment competition in the field of tourism, especially the tour and travel agencies to karimunjawa characterized by the emergence of many Bureau of tour and travel agencies in recent years. Tour and Travel Karimunjawa Beach Adventure decreased sales volume in the last two years, 2012 and 2013.The research was conducted at the Bureau of Tour and Travel Karimunjawa Beach Adventure. This study aimed to determine the effect of three variables: price (X1), promotion (X2), and quality of service (X3) of sales volume (Y). In this research, data was collected by tools such as questionnaires given to 100 respondents, which aims to determine the respondentâ€™s responses to each variable. The analysis includes the validity test, reliability, classical assumption test (normality test, multicolinearity test, heteroskedaktisitas test), multiple linear regression analysis and goodness of fit test (F-test, t test, the coefficient of determination)From the result of regression analysis can be know that variables ofÂ price, promotion, and quality of service are all have positive effect on the volume of sales in the Bureau of Tour and Travel Karimunjawa Beach Adventure in which price is the most influential variable to sales volume, followed by promotion and quality of service, three variables The effect of 64.3% of the sales volume, while the remaining 35.7% is influenced by other variables.